National Trends in the Prevalence of Unmet Health Care and Dental Care Needs During the COVID-19 Pandemic: Longitudinal Study in South Korea, 2009-2022 - Yeji Kim; Soeun Kim; Somin Lee; Jaeyu Park; Ai Koyanagi; Lee Smith; Min Seo Kim; Guillaume Fond; Laurent Boyer; Guillermo Felipe López Sánchez; Elena Dragioti; Hyeon Jin Kim; et al. (JMIR Publications, 2024)
BackgroundAlthough previous studies have investigated trends in unmet health care and dental care needs, most have focused on specific groups, such as patients with chronic conditions and older adults, and have been limited by smaller data sets. ObjectiveThis study aims to investigate the trends and relative risk factors for unmet health care and dental care needs, as well as the impact of the COVID-19 pandemic on these needs. MethodsWe assessed unmet health care and dental care needs from 2009 to 2022 using data from the Korea Community Health Survey (KCHS). Our analysis included responses from 2,750,212 individuals. Unmet health care or dental care needs were defined as instances of not receiving medical or dental services deemed necessary by experts or desired by patients. ResultsFrom 2009 to 2022, the study included 2,700,705 individuals (1,229,671 men, 45.53%; 673,780, 24.95%, aged 19-39 years). Unmet health care needs decreased before the COVID-19 pandemic; however, during the pandemic, there was a noticeable increase (βdiff 0.10, 95% CI 0.09-0.11). Unmet dental care needs declined before the pandemic and continued to decrease during the pandemic (βdiff 0.23, 95% CI 0.22-0.24). Overall, the prevalence of unmet dental care needs was significantly higher than that for unmet health care needs. While the prevalence of unmet health care needs generally decreased over time, the β difference during the pandemic increased compared with prepandemic values. ConclusionsOur study is the first to analyze national unmet health care and dental care needs in South Korea using nationally representative, long-term, and large-scale data from the KCHS. We found that while unmet health care needs decreased during COVID-19, the decline was slower compared with previous periods. This suggests a need for more targeted interventions to prevent unmet health care and dental care needs.